Fluorescence Changes of Glycyl-Tryptophan Peptide in the Presence of Some Newly Synthesized Azobenzene Compounds - Ciobanu, Catalina-Ionica; Habasescu, Laura; Scutaru, Dan; Drochioiu, Gabi (Letters in Organic Chemistry, 2015)
Five newly synthesized bent-shaped compounds containing azobenzene chromophores have been prepared by resorcinol esterification with 4-(4-alkyloxyphenylazo) benzoic acid using DCC and DMAP. The structure of newly synthesized compounds was confirmed by MS and FT-IR spectroscopy. In addition, NMR spectroscopy also established the purity of these compounds. According to their azo-type chemical structure, the newly synthesized compounds are expected to be highly fluorescent. Consequently, their absorption and fluorescence properties were investigated using UVVis and fluorescence spectroscopy. The present paper also investigates the fluorescence evolution of glycyl-L-tryptophan dipeptide at different concentrations of the newly synthesized bent-shaped compounds. The intensity of their fluorescence band over 400 nm depends much on individual structures. Since the investigated compounds could have optical properties characteristic to liquid crystals, the interaction with fluorescent peptides, such as glycyl-tryptophan or proteins might enhance their utility.
Keywords: Azobenzene compounds